THE CONTROL OF LAND USE AND UTILIZATION IN KUPANG REGENCY THROUGH THE LAW FORMATION - Wini Dina Retriani Lani (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Demand for land in Kupang Regency keeps increasing while the land availability is limited and the changes in the utilization continues. If it is not controlled, there will be a gap between economic orientation and the environmental sustainability. However, the control does not work due to the absence of legal instruments such as Regional Regulation which regulates this issue. To answer these legal issues, the researchers applied empirical juridical research methods while the analysis method is prescriptive juridical. The research shows that the control of land use and utilization in Kupang Regency is not effectively implemented because Regional Regulation of Detailed Spatial Plan of Regency and Spatial Plan of Strategic Area, the utilization license and the change of land use license have not been formulated. Moreover, an integrated license process is not effectively applied which caused several constructions are built prior to the license granted, unclear boundary between forest and non-forest area, incomplete data base of agriculture, farm, and absentee land.Keywords: control, land use, land utilization